Evaluación del comportamiento del MSE (energía mecánica específica) implementando el motor de fondo D&J en operaciones de perforación de las formaciones A1, A2 Y ALPHA en un pozo del campo J1 de la Cuenca Caguán – Putumayo. (2021)
In the process of drilling an oil well, it is required that the design of the drillstring be adequate and that its properties according to the desired parameters are optimal in order to reduce times and therefore operating costs. The low performance of the MSE (Specific Mechanical Energy) in the drilling of the formations (A1, A2 and ALPHA) in the J1 field of Putumayo presents a greater impact during drilling when crossing formations with conglomerate environments that have sand and clay intercalations, Because its behavior is difficult to predict and controlled parameters must be kept in order to generate better drilling times with precise and optimal variables. In this sense, the objective of this project is to evaluate the behavior of the MSE (specific mechanical energy) through the best operating ranges of WOB, ROP, Gallonage, Torque and RPM in the formations to be evaluated. With the identification of the optimal parameters of these variables, it is sought that the MSE reflects values ​​of (100 - 200 Kpsi) in the A1 formation, (100-600 Kpsi) for the A2 formation and (100 - 900 Kpsi) in the ALPHA formation.